2018
DOI: 10.5195/ijms.2018.41
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication among Undergraduate Medical Students of Alexandria Faculty of Medicine: Where do We Stand?

Abstract: Background: The aim of the present study was to assess the prevalence of self-medication among undergraduate medical students in Alexandria Faculty of Medicine and recognize the patterns and the attitude of students towards intake. Methods: A cross-sectional study was conducted among undergraduate medical students attending Alexandria Faculty of Medicine from both national and international programs during the period of June 2013 until October 2013. A self-administrated, semi-constructed questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…High self-medication prevalence was reported among university students in Bangladesh (88%), 5 Jordan (86.7%), 6 Saudi Arabia (86%), 7 and Egypt (52.7%). 8 Similarly, a study conducted among students of Gadjah Mada University, Indonesia 9 and Jiangsu University, China 10 revealed that self-medication with antibiotics was practiced by 49% and 47.9% of the respondents, respectively. In Ethiopia, the prevalence of self-medication among university students across studies has been 32.7%-70.8%.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…High self-medication prevalence was reported among university students in Bangladesh (88%), 5 Jordan (86.7%), 6 Saudi Arabia (86%), 7 and Egypt (52.7%). 8 Similarly, a study conducted among students of Gadjah Mada University, Indonesia 9 and Jiangsu University, China 10 revealed that self-medication with antibiotics was practiced by 49% and 47.9% of the respondents, respectively. In Ethiopia, the prevalence of self-medication among university students across studies has been 32.7%-70.8%.…”
Section: Introductionmentioning
confidence: 98%
“…11,13,16,17 Antibiotics, analgesics, antipyretics, antacids, vitamins, cough remedies, eye drops, antihistamines, antimicrobials, and anti-inflammatory drugs are commonly used classes in selfmedication. 8,[11][12][13]18,19 Inappropriate self-medication is a public-health problem worldwide. 20 In developing countries, most illnesses are treated by self-medication, bringing much public and professional concern about irrational use of medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Total score ranged between 0 to 7; Since poor level considered for the total score (0, 1, 2, 3 and 4) out of (7) and good level considered for the total score (5, 6 and 7) out of (7) The third section assesses the attitudes of students towards SM. Five-point Likert scale items were used; strongly agree responses were scored as 5, agree as 4, uncertain as 3, disagree as 2, and strongly disagree as 1.…”
Section: Participants and Survey Instrumentmentioning
confidence: 99%
“…Total score knowledge ranged between 0 to 7; Since poor level considered for the total score (0, 1, 2, 3 and 4) out of ( 7) and good level considered for the total score (5, 6 and 7) out of (7). Results shows that 17 students out of 316 which represent 5.4% of the total sample had poor knowledge of SM with total score less than 5, while 299 ss, which represent 94.6% had good knowledge of SM with total score (5 and above).…”
Section: Knowledge Of Self-medicationmentioning
confidence: 99%
See 1 more Smart Citation